Fraud Issues in the National Health Insurance (Causes, Legal Impacts, Dispute Settlement and Preventive Measures) - Yohanes Firmansyah; Imam Haryanto; Ernawati Ernawati (Jurnal Multidisiplin Madani, 2022)
National Health Insurance which covers all financing of health services in terms of national insurance. This causes the National Health Insurance to manage a very large amount of money and has an impact on many challenges regarding overcoming fraud committed by various parties. This research is a literature search that analyzes the concept of fraud, legal impact, dispute resolution, and preventive actions in dealing with and preventing fraud. The legal basis used is very diverse, starting from the regulations governing national health insurance, as stated in Presidential Regulation no. 12 of 2013 concerning Health Insurance and the Law of the Republic of Indonesia Number 24 of 2011 concerning the Social Security Administering Body; The legal implications contained in the criminal code of law; and prevention of fraud as regulated in PERMENKES RI 269/MENKES/PER/III/2008 concerning Medical Records and Regulation of the Minister of Health of the Republic of Indonesia Number 36 of 2015 concerning Prevention of Fraud in the Health Insurance Program in the National Social Security System